Consumption of Drinks as Representation of Community in the Culture of Nobility of the 17th–18th Centuries - Laužikas, Rimvydas (Tautosakos darbai, 2016)
Drinks and customs related to their consumption play a special role in the social history (essentially, that of the human community). However, research of the customs of alcohol consumption in Lithuania (along with the history of daily life in general and the culture of the nobility’s daily life in particular) is rather sporadic so far. The article presents a research work in cultural anthropology on the alcohol consumption as means (or prerequisite) of achieving more important aims of religious, social, economic or other kind. Because of the big scope of research and low level of prior investigation, the subject of this article is limited to a single aspect – namely, the custom of drinking from the same glass; to the culture of only one social layer of the Grand Duchy of Lithuania (GDL) – the nobility; and to a distinct period – the 17th–18th centuries. The aim of analysis is revealing sources of this custom, its development and meaning in the social community of the given period.According to the research, the GDL presented a sphere of interaction between the local pre-Christian Lithuanian culture, which had been developing for an incredibly long period – even until the end of the 15th century, and the Western European cultural tradition. The Western European culture, formed in the course of joining together elements of the antique heritage, the Christian worldview and the inculturized “Northern barbarism”, acquired in the 14th–16th century Lithuania one of its essential constituents – namely, the culture of the “Northern barbarism” still alive and functioning. On the other hand, the nobility of the GDL, raised in pre-Christian Lithuanian culture, had no trouble recognizing elements of its local heritage in the Western Christian culture. The local custom of drinking from the same glass characteristic to the higher social layers supposedly stemmed from the drinking horns. Along with Christianity and spread of the wine culture, the local pre-Christian custom of drinking from the same glass should have been abandoned by the nobility, surviving instead solely in the lower social classes. The western custom of drinking from the same glass spread in Lithuania along with Christianity and the wine consumption. However, its influence on the nobility was rather limited. In the 15th–16th centuries, when this custom was still rather widespread in Europe, the Lithuanian nobility was just beginning its acquaintance with the wine culture, while in the 17th–18th centuries, when the wine culture grew popular in Lithuania, the western-like custom of drinking from the same glass had already waned in other European countries. Therefore, the western custom of drinking from the same glass was rather a marginal phenomenon among the Lithuanian nobility, affected by the cultural exchange with the Polish nobility (which grew especially intense following the union of Lublin) and the ideology of Sarmatianism. The custom of drinking from the same glass disappeared in the culture of the Lithuanian nobility at the turn of the 18th–19th century due to the ideas of Enlightenment and the altered notions of healthy lifestyle and hygiene. However, drinking from the same glass, as a distant echo of the ancient customs representing social community was quite popular in the peasant culture as late as the end of the 20th – beginning of the 21st centuries.
Keywords: -